Perceptions on the concept of Mediterranean diet and its evolution - perspectives of professionals from the Algarve-Portugal - Helena Real; Pedro Graça (Universidad Carlos III de Madrid, 2020)
Introduction: Defining a concept well is important to facilitate the transmission of a coherent message that lasts over time. Objectives: To develop a conceptual map of the Mediterranean Diet definition; to evaluate perceptions about the concept and evolution of the Mediterranean Diet of personalities representative of the Mediterranean Diet, Algarve-Portugal. Methodology: Thirteen semi-structured interviews were applied. The audio was recorded, transcribed, thematically coded and the interviewees' indications were listed. The analysis of the concept was carried out based on the hybrid method, in three phases: theoretical, empirical and analytical. Results: Crossing the content of the interviews with the literature, a conceptual map of the definition of the Mediterranean Diet was developed with four axes - food, conviviality, food production, lifestyle - representing a cultural model, impacting on areas such as environment, economy, health and tourism. The interviewees indicated that there is an evolution of the Mediterranean Diet concept, in keeping with the constant technological and research innovation, taking care of the distortion of the concept and its preservation. Conclusions: This paper presents, for the first time, the perceptions of Portuguese professionals on the definition and evolution of the Mediterranean Diet, being the conceptual map an innovative model and a facilitator of the Mediterranean Diet definition communication.